(untitled) (Dhaka University Journal of Science, 2012)
In this paper the performance of a PV driven water pump, without battery storage, for supplemental irrigation by harvesting rainwater is analyzed. A brushless DC motor is used in this work. The worst day, in terms of rainfall, of the month of July has been chosen for data collection. The variation of the flow rate as a function of the PV array power is found to be linear. Head loss is calculated and found greater at higher flow rate. Lower trend of the subsystem efficiency is observed with the increment of the array power. Considering the module efficiency of the manufacturer, the system efficiency is also calculated and found 3.2% as the highest. The amount of water lifted is found to be quite satisfactory for supplemental irrigation. DOI: http://dx.doi.org/10.3329/dujs.v60i1.10333 Dhaka Univ. J. Sci. 60(1): 37-41, 2012 (January)